2003
DOI: 10.1002/hc.10147
|View full text |Cite
|
Sign up to set email alerts
|

The design and synthesis of β‐trifluoromethylenol phosphates as potential insecticides

Abstract: A new group of compounds, ␤-trifluoromethylenol phosphates [(RO) 2 P(O)OCR CHCF 3 ], has been designed and prepared by several methods. Some of them showed good insecticidal activities. In the molecular structure, the designed leaving group can rearrange to a powerful electrophilic agent, ␤,␤-difluorovinyl ketone, which would be a potential enzyme inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The addition reaction is accelerated by electron-donating substituents, and alkenes react faster than alkynes under identical reaction conditions. The described reaction is suitable for the synthesis of new trifluoromethyl substances, which are important synthetic targets in pharmaceutical and agrochemical industries , using inexpensive substrates ( 2 – 3 ) and easily handleable CF 3 source 1a .…”
mentioning
confidence: 99%
“…The addition reaction is accelerated by electron-donating substituents, and alkenes react faster than alkynes under identical reaction conditions. The described reaction is suitable for the synthesis of new trifluoromethyl substances, which are important synthetic targets in pharmaceutical and agrochemical industries , using inexpensive substrates ( 2 – 3 ) and easily handleable CF 3 source 1a .…”
mentioning
confidence: 99%
“…2,2-Dibromo-1-arylethanones are used in organic synthesis primarily for the construction of heterocyclic structures [1][2][3] and small rings, [4][5][6] for the preparation of compounds with a double [7][8][9] or triple 10 bond, and in reactions with phosphorous esters 11,12 and thiols. 13,14 Most of the known methods for the synthesis of 2,2-dibromo-1arylethanones are based on bromination of acetophenones with molecular bromine 8,11,[15][16][17][18] and its complex compounds. 19,20 In the last two decades, chlorination and bromination of organic compounds with HCl or HBr combined with peroxides have developed extensively.…”
mentioning
confidence: 99%
“…Utimoto research group, reported the glycidic ester (α,β‐epoxyketones) type condensation by reacting the in situ generated lithium enolate 74 a with aryl aldehyde in an intermolecular Aldol reaction followed by epoxide formation (Scheme B). Huang and his co‐workers, also synthesized potent insecticides, such as β‐trifluoromethylenol phosphates 75 via coupling reaction of in situ generated β‐bromoenol phosphates 76 a with CF 3 reagent (Scheme C). Shchepin et al., synthesized spirocyclopropane fused indanones 77 a and dihydronaphthones 77 b from corresponding α,α‐dihaloketones 78 by trapping the in situ generated zinc‐enolates 78 a/b with an electron‐deficient olefins (Scheme D).…”
Section: αα‐Dihaloketones As Building Blocks In Organic Synthesismentioning
confidence: 99%